Dome: parallel programming in a distributed computing environment - Arabe, J.N.C.; Beguelin, A.; Lowekamp, B.; Seligman, E.; Starkey, M.; Stephan, P. (Parallel Processing Symposium, 10th International (IPPS '96, 1996)
The Distributed object migration environment (Dome) addresses three major issues of distributed parallel programming: ease of use, load balancing, and fault tolerance. Dome provides process control, data distribution, communication, and synchronization for Dome programs running in a heterogeneous distributed computing environment. The parallel programmer writes a C++ program using Dome objects which are automatically partitioned and distributed over a network of computers. Dome incorporates a load balancing facility that automatically adjusts the mapping of objects to machines at runtime, exhibiting significant performance gains over standard message passing programs executing in an imbalanced system. Dome also provides checkpointing of program state in an architecture independent manner allowing Dome programs to be checkpointed on one architecture and restarted on another.